peran brand awareness sebagai mediasi pemasaran digital dan customer review terhadap keputusan pembelian di nesh navya - Ni Kadek Denda Clarisa Faradita; I Gusti Ngurah Oka Ariwangsa; Nilna Muna; Putu Ayu Titha Paramita Pika (Ikatan Da'i Indonesia, 2025)
This study aims to empirically test and analyze the strategic role of Brand Awareness as a mediating variable in influencing the relationship between Digital Marketing and Customer Reviews on Purchasing Decisions among Nesh Navya consumers. This study uses a quantitative approach with a survey method, where data is collected from respondents through a structured questionnaire and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) through SmartPLS software. The results show that Digital Marketing and Customer Reviews have a significant positive influence on the formation of Brand Awareness, and Brand Awareness is also proven to be significant in driving Purchasing Decisions. Crucial findings confirm that Brand Awareness plays an effective partial mediation role; the combined effect of Digital Marketing and Customer Reviews on Purchasing Decisions becomes substantially stronger through the strengthening of Brand Awareness. Therefore, it is concluded that Brand Awareness at Nesh Navya is not only the result of marketing activities, but is a critical bridge that integrates digital initiatives and the credibility of consumer reviews into real transaction decisions, so the company is advised to continue prioritizing investment in strategies that strengthen brand visibility and awareness on an ongoing basis.